Investigation of Fe3O4/SBA-15 magnetic nanocomposite synthesized by microwave-assisted solvothermal route as multi-therapeutic agent - Emadi, Hamid; Hemmati, Amir; Behrouzi, Erfan (Journal of Composites and Compounds, 2022)
In the current study, a facile and in situ synthesis route for the preparation of mesoporous SiO2-Fe3O4 magnetic nanocomposite using iron (III) acetylacetonate via microwave-assisted solvothermal method is proposed. To characterize the samples, XRD, EDS, SEM, TEM, BET, and VSM were applied, and their potential applications as drug carriers, hyperthermia, and MRI contrast agents were investigated. The results confirmed that the magnetic nanocomposite could be used as a drug carrier, and its drug release rate is affected by the magnetic field. Also, the product applications as both hyperthermia and MRI contrast agent for T2 weighted images were approved.